Modulatory Effect of Probiotic Lactobacillus rhamnosus PB01 on Mechanical Sensitivity in a Female Diet-Induced Obesity Model - Hiva Alipour; Parisa Gazerani; Mahmoud Heidari; Fereshteh Dardmeh (Pain Research and Management)
Obese animals and humans demonstrate higher sensitivity to pain stimuli. Among the endogenous factors prompting obesity, the intestinal microbiota has been proposed to influence responsiveness to pain. The beneficial effects of probiotics on obesity are well documented, whereas data on their analgesic efficacy is minimal. The protective effect of probiotics on nociception in diet-induced obese male mice has been previously demonstrated, but the sex differences in pain sensitivity and analgesic response do not allow for the generalization of these findings to the female gender. Hence, this study aimed at investigating the potential effects of oral probiotic supplementation on mechanical pain thresholds in female diet-induced obese mice compared with controls. Thirty-two adult female mice (N=32) were randomly divided into two groups receiving standard (normal-weight group; NW) or high-fat diet (diet-induced obesity; DIO). All rats received a single daily dose (1 × 109 CFU) of probiotics (Lactobacillus rhamnosus PB01, DSM14870) for four weeks by gavage. Mechanical pain thresholds were recorded by an electronic von Frey device at baseline, at the end of weeks 2, 4, 6, and 8 in both DIO and NW groups with and without consumption of probiotics. Blood samples were obtained for the measurement of lipid profile and reproductive hormone levels. Bodyweight was considerably lower (P<0.001) in groups supplied with probiotics than groups without probiotics. Pressure pain threshold values showed a significant (P<0.001) increase (reduced pain sensitivity) following probiotic supplementation, proposing a modulatory effect of probiotics on mechanical sensory circuits and mechanical sensitivity, which might be a direct consequence of weight loss or an indirect result of the probiotics’ anti-inflammatory properties. Understanding the precise underlying mechanism for the effect of probiotics on weight loss and mechanical pain sensitivity seen in this study warrants further investigation.